Trends in Islamic Education Models for Promoting Tolerance in Multicultural Contexts - Heru Wibowo; Bunyamin; Mohamad Ali (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to examine global research trends, intellectual structures, and future directions concerning IRE learning models that promote tolerance through a comprehensive bibliometric analysis. The growing cultural and religious diversity of contemporary societies has intensified the need to integrate multicultural values into Islamic Religious Education (IRE) to cultivate tolerance and peaceful coexistence. Theoretical framework: The theoretical framework integrates multiculturalism theory, Islamic pedagogy, and cross-cultural competence to explain how inclusive educational practices strengthen intercultural understanding and religious moderation. Literature review: Previous studies have emphasized the importance of multicultural education in reducing prejudice and fostering social harmony; however, they remain fragmented, predominantly localized, and rarely provide a comprehensive mapping of global scholarly developments. Method: To address this gap, this study employs a bibliometric approach using Scopus-indexed publications filtered through the PRISMA 2020 protocol. A total of 459 eligible articles were analyzed using the Bibliometrix package and Biblioshiny interface in RStudio to examine publication growth, citation patterns, collaboration networks, thematic evolution, and emerging research trends. Results: The findings reveal a substantial increase in publications after 2020, indicating growing scholarly attention to multicultural Islamic education. Social sciences emerged as the dominant disciplinary field, while Indonesia contributed the largest number of publications and demonstrated expanding international collaboration, particularly with Australia, the United Kingdom, and the United States. Thematic analysis identifies multiculturalism, tolerance, and multicultural education as established research clusters, whereas humanistic education, intercultural competence, and cultural-religious awareness represent promising future research directions. Implications: These findings imply that policymakers, curriculum developers, and educators should strengthen inclusive pedagogical approaches that integrate multicultural competencies into IRE curricula to support sustainable social cohesion. Novelty: The novelty of this study lies in proposing an integrated conceptual framework that synthesizes multiculturalism theory, Islamic pedagogy, and cross-cultural competence, providing a comprehensive reference for future research and educational policy aimed at fostering tolerance in increasingly pluralistic societies while contributing to the achievement of the Sustainable Development Goals.